Perception and Management of Mango (Mangifera indica L.) Dieback Disease in Actopan, Veracruz, Mexico - Noa-Carrazana, Juan Carlos (2025)
Introduction. Dieback is a severe disease reported in mango-producing regions of Mexico; however, there is limited information regarding growers’ perception and management of this disease. Objective. To assess mango growers’ perception and management practices regarding dieback disease in the municipality of Actopan, Veracruz, Mexico, while describing their socioeconomic and production characteristics. Materials and methods. The research was conducted in the municipality of Actopan, Veracruz, Mexico, during 2021-2022. Semi-structured interviews consisting of 45 questions were conducted with mango growers. The study addressed growers’ socioeconomic characteristics, orchard management practices, recurring diseases, and their perception and management of mango dieback. Data analysis was performed using various multivariate and descriptive statistical tools. Results. Most mango growers were men (94 %) with a wide age range, predominantly consisting of elderly and young adults. Cluster analysis revealed three distinct groups of producers: small (56 %), medium (16 %), and large (28 %), each with specific characteristics regarding cultivated area, agronomic management, and yield (M = 8.54 ± 3.75 t/ha). Dieback was recognized by all interviewed growers, who identified gummosis, branch rot, and trunk rot as the main symptoms associated with the disease. Only 18.75 % of growers implement specific management or control measures through chemical and mineral fungicides. Conclusions. For mango growers in Actopan, Veracruz, dieback represents a disease of major importance in their cultivation. While growers implement basic management strategies, these have proven inefficient, driving interest in developing new and improved control tools.